Cross-Platform Development: Software that Lasts. - Bishop, Judith; Horspool, Nigel (Computer (00189162), 2006)
The article discusses the design of software that is easy to port or is created for multiple platforms or language or operating systems. The authors reflect that the design of software for multiple platforms that is easy to port is a neglected area of software engineering. Their proposed solution is the use of middleware that is constructed using reflection and is controlled through XML specifications. This could give components in a large software system a language dependence and a high degree of platform. This could then result to the ability of the software to shift easily as platforms change and improve and thereby reducing cost of future changes.